Environmental and Economic Evaluations of Building Energy Retrofits - Hou, Cynthia; Lai, Joseph H.K (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book comprises six papers published in the Special Issue "Environmental and Economic Evaluations of Building Energy Retrofits". The six papers each adopt different perspectives in investigating building energy retrofit practices in Hong Kong, Poland, the Netherlands, Finland, and Italy. The target of the studies includes campus buildings, renovation options for modernist housing estates, green building certification schemes, practitioners' views and practices, and energy system performance.